2007
DOI: 10.1002/jmri.20974
|View full text |Cite
|
Sign up to set email alerts
|

Uterus‐like mass: MRI appearance of a very rare entity

Abstract: We describe a 37-year-old patient who presented with right lower quadrant pain and intermenstrual bleeding. MRI demonstrated a 5 ϫ 5 cm lobulated mass centered in the right uterine wall interpreted as suspicious for malignancy. A total hysterectomy was performed, and the gross and histologic features were consistent with the diagnosis of a uterus-like mass. Uterus-like mass is a benign entity that can be found in a variety of organs, and is characterized by endometrium surrounded by smooth muscle. It is an ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 16 publications
0
35
0
Order By: Relevance
“…Twenty-three cases of a uterus-like mass had been reported as of September 2010 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). A total of 24 cases including the present case are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 90%
“…Twenty-three cases of a uterus-like mass had been reported as of September 2010 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). A total of 24 cases including the present case are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 90%
“…Uterus‐like mass is an extremely rare benign pathological entity of uncertain histogenesis 1–13 . Although the ovary is the initially described 1 and most commonly reported site for development of a uterus‐like mass, 1,2 the disorder has been known to occur in the various genital and extragenital locations 3–13 . When definitive diagnosis of uterus‐like mass is made, it should be differentiated from extrauterine adenomyoma 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Uterus‐like mass composed of a cavity lined by mucosa resembling endometrium and surrounding thick smooth muscle layer simulating myometrium is an extremely rare disease entity of which the histogenesis is presently unknown 1–13 . As uterus‐like mass possesses well‐organized structure resembling normal uterine corpus, it should be carefully differentiated from extrauterine adenomyoma, which lacks a uterus‐like organization 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Various theories have been proposed to explain the occurrence of uterus-like masses at different sites, including (1) metaplastic change of ovarian stromal cells and (2) congenital anomalies of the müllerian duct system [9]. However, these theories cannot account for this entity occurring within the conus medullaris, in association with cord tethering.…”
Section: Discussionmentioning
confidence: 99%
“…Menn et al [9] described magnetic resonance imaging findings in a case of uterus-like mass situated in the broad ligament. They suggested that the findings of a circumscribed area isointense to the endometrium and surrounded by a low signal junctional zone and a zone isointense to the myometrium, similar to the zonal anatomy of the uterus, should raise the suspicion of this diagnosis.…”
Section: Discussionmentioning
confidence: 99%